Therapeutic Effect of Traditional Chinese Medicine on a Rat Model of Branch Retinal Vein Occlusion - Pan Long; Weiming Yan; Jianwen Liu; Manhong Li; Tao Chen; Zuoming Zhang; Jing An (Journal of Ophthalmology)
Branch retinal vein occlusion (BRVO) is a common retinal vascular disorder leading to visual impairment. Currently, the general strategies for BRVO are symptomatic therapies. Cardiovascular aspects are essential risk factors for BRVO. The traditional Chinese medicine hexuemingmu (HXMM), consisting of tanshinol and baicalin, dilates the vasculature and accelerates microcirculation. Therefore, the aim of this study was to determine the efficacy and possible mechanism of HXMM in a BRVO rat model established by laser photocoagulation. Successful BRVO rat models were treated with different doses of HXMM. Fundus photography and fluorescein fundus angiography (FFA) of the animals were applied. The retinal layers were measured by optical coherence tomography (OCT). Full-field electroretinography (ffERG) was applied to evaluate the retinal function. The ear vein flow velocity was measured via a microcirculation detector. The expression of the vascular endothelial growth factor (VEGF-α) was measured via western blotting and immunofluorescent staining. Our study found that retinal edema predominantly occurred in the inner nuclear layer (INL) and outer nuclear layer (ONL). The retinal edema of the treated groups was significantly relieved in the early stage of BRVO as visualized via OCT detection and HE staining. The amplitudes of the b wave and oscillatory potentials (OPs) waves of ffERG in the treated groups were increased compared with those of the control group at several detection points (3, 5, 7, 10, 14, and 21 d postocclusion). The expression of VEGF-α was reduced in the treated groups at an early stage of BRVO. Furthermore, the ear vein flow velocity of the HXMM treatment groups was faster than that of the control group. Thus, our study indicates that the traditional Chinese medicine HXMM could ameliorate retinal edema and rescue the retinal structure and function in BRVO models through promoting occluded vein recanalization, improving microcirculation, and regulating the expression of VEGF-α.